An Extremely Rare Case Report of Aphallia with Horseshoe Kidney and Ureterohydronephrosis [Letter] - Picos-Cárdenas VJ; Leal-Ugarte E; Meza-Espinoza JP (International Medical Case Reports Journal, 2024)
Verónica Judith Picos-Cárdenas,1 Evelia Leal-Ugarte,2 Juan Pablo Meza-Espinoza2 1Laboratorio de Genética, Facultad de Medicina, Universidad Autónoma de Sinaloa, Culiacán, Sinaloa, C. P. 80030, México; 2Facultad de Medicina Matamoros, Universidad Autónoma de Tamaulipas, Matamoros, Tamaulipas, C. P. 87300, MéxicoCorrespondence: Juan Pablo Meza-Espinoza, Facultad de Medicina Matamoros, Universidad Autónoma de Tamaulipas, Matamoros, Tamaulipas, México, Tel +528682044000, Email sirol1073@yahoo.com.mx